MANIFESTATIONS OF AGGRESSION IN YOUNG PEOPLE - Xolboyeva Surrayyo Alisher qizi; Seytniyazova Alfiya Bekpolat qizi; Palvasheva Mubarek Xazilbekovna; Azirbaev Ótkirbay Mińbay uli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this article provides information about aggression and its manifestation.